PROBLEMS OF TRANSLATING PHRASEOLOGICAL UNITS FROM ENGLISH INTO UZBEK LANGUAGE - Muxammadova Dilnoza Dilmurod qizi; Umaraliyeva Munojatxon (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article describes the problems encountered in translating phraseological units from Uzbek to English language and explained by many examples.